2013
DOI: 10.1007/s10661-013-3394-x
|View full text |Cite
|
Sign up to set email alerts
|

Community air monitoring for pesticides. Part 3: using health-based screening levels to evaluate results collected for a year

Abstract: The CA Department of Pesticide Regulation (CDPR) and the CA Air Resources Board monitored 40 pesticides, including five degradation products, in Parlier, CA, to determine if its residents were exposed to any of these pesticides and, if so, in what amounts. They included 1,3-dichloropropene, acrolein, arsenic, azinphos-methyl, carbon disulfide, chlorpyrifos and its degradation product, chlorthalonil, copper, cypermethrin, diazinon and its degradation product, dichlorvos, dicofol, dimethoate and its degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 6 publications
0
22
0
1
Order By: Relevance
“…[35] This was confirmed by a monitoring study conducted in a small community where Cal EPA placed air monitors on elementary school roofs over a one-year period and detected twenty-three pesticides known to be applied in the area according to the CA-PUR system. [36] Additionally, a northern California study found that crops within 1500m of homes predicted carpet dust levels of pentachlorophenol and DDE. [37] Thus, pesticides from agricultural applications find their way into homes, exposing residents in agricultural communities to pesticides, even those not involved in agricultural work.…”
Section: Introductionmentioning
confidence: 99%
“…[35] This was confirmed by a monitoring study conducted in a small community where Cal EPA placed air monitors on elementary school roofs over a one-year period and detected twenty-three pesticides known to be applied in the area according to the CA-PUR system. [36] Additionally, a northern California study found that crops within 1500m of homes predicted carpet dust levels of pentachlorophenol and DDE. [37] Thus, pesticides from agricultural applications find their way into homes, exposing residents in agricultural communities to pesticides, even those not involved in agricultural work.…”
Section: Introductionmentioning
confidence: 99%
“…Much in the same way as these, seven other papers 12,13,15,[20][21][22][23] addressed the issue of air contamination by pesticides from the perspective of environmental sciences (environmental monitoring and risk analysis and assessment), while the methodology for assessing the impact and risk of exposure frequently observed in these studies includes, somehow, analyses of public health interest, such as the estimation of risk or carcinogenic potential related to exposure to pesticides, according to risk assessment methodologies proposed by international agencies of the environmental or health sector, such as the U.S. Environmental Protection Agency (US EPA) and the World Health Organization (WHO). • 28 papers…”
Section: Resultsmentioning
confidence: 62%
“…Air measurements of chlorpyrifos in a town located near agricultural fields exhibited a direct variation with the amount of this pesticide applied within an 8 km buffer (Fig. ) [Wofford et al, ]. Similar high correlations were observed for air concentrations of numerous other pesticides compared with amounts known to have been applied, establishing drift at distances similar to those used as buffers in research studies on child development.…”
Section: Methodologic Challengesmentioning
confidence: 69%
“… Comparison of average weekly concentrations of chlorpyrifos detected at three monitoring sites in a rural California town over a one‐year period, and total reported use of chlorpyrifos by week in an 8 km study area surrounding the monitoring sites. Reproduced from Wofford et al []. (Reprinted with permission from Springer.)…”
Section: Methodologic Challengesmentioning
confidence: 99%